2016
DOI: 10.1186/s13063-016-1541-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the vascular protective effects of new oral anticoagulants in high-risk patients with atrial fibrillation (PREFER-AF): study protocol for a randomized controlled trial

Abstract: BackgroundAtrial fibrillation (AF) is known to be associated with several pathophysiological mechanisms including endothelial dysfunction of the heart and arterial vessels. Recent evidence suggests that new oral anticoagulant (NOAC) treatment may improve endothelial function and the inflammatory process involved in atherosclerosis in AF patients. This study is designed to determine the efficacy of NOAC therapy in the prevention of endothelial dysfunction and the progression of atherosclerosis of AF subjects.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Although the semaglutide trial showed significant beneficial effects on nonfatal stroke, the cardiovascular outcome trials were underpowered for the specific stroke endpoints. More studies using ertugliflozin (SGLT2 inhibitor) and dulaglutide (once-weekly GLP1 analogue) are currently ongoing in the hope of improving vascular outcomes and total mortality in patients with diabetes at high stroke risk [83,84]. Until the results of these studies are released, multifactorial interventions targeting individual cerebrovascular risk factors are required to improve clinical outcomes in diabetes patients after a stroke or at high risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Although the semaglutide trial showed significant beneficial effects on nonfatal stroke, the cardiovascular outcome trials were underpowered for the specific stroke endpoints. More studies using ertugliflozin (SGLT2 inhibitor) and dulaglutide (once-weekly GLP1 analogue) are currently ongoing in the hope of improving vascular outcomes and total mortality in patients with diabetes at high stroke risk [83,84]. Until the results of these studies are released, multifactorial interventions targeting individual cerebrovascular risk factors are required to improve clinical outcomes in diabetes patients after a stroke or at high risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Additively, Kim et al ( 16 ) have been planning a randomized prospective study, with the aim of evaluating the effects of dabigatran and rivaroxaban on endothelial intima, medial thickness, and atheroma plaques in carotid artery in patients with atrial fibrillation. Warfarin will be administered to control group.…”
Section: Discussionmentioning
confidence: 99%
“…The ending date was determined as 2018. Within this study, same processes end-up with restenosis will be assessed in humans ( 16 ). Apparently, this trial has a great importance as it is first study in humans assessing rivaroxaban effect on intimal and medial changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, these hypotheses will have to be further proved in newer randomized trials beginning with the PREFER-AF trial which should be the first randomized trial evaluating vascular protective effects of these DOACs [25]. The overall use of these DOACs will also depend on several factors such as patient satisfaction, cost, and risk profile of patients.…”
Section: Discussionmentioning
confidence: 99%